Adolescent Health Awareness Through Digital-Based Youth Posyandu: Peningkatan Kesadaran Kesehatan Remaja Melalui Posyandu Remaja Berbasis Digital - Anggriani, Devi; Sukmana, Hendra (Indonesian Journal of Cultural and Community Development, 2025)
Background: Adolescent health issues such as early marriage, anemia, and stunting remain significant public health challenges in Indonesia. To address this, the government has developed the Posyandu Remaja program as an integrated platform for youth health education. Specific Background: The study examines how health education innovations—specifically online game–based media—are applied in the Estu Jadi Dipuja youth health initiative to improve adolescents’ knowledge and engagement. Knowledge Gap: Despite national guidelines for Posyandu Remaja, implementation gaps remain due to limited training of youth cadres and a lack of engaging educational tools. Aims: The study aims to analyze the implementation and outcomes of early stunting education using online game media at Posyandu Remaja as a participatory health model. Results: Findings show that interactive digital media significantly increased youth participation and understanding of stunting prevention. Youth cadres demonstrated improved facilitation skills and stronger peer involvement. Novelty: The integration of digital game media into youth health promotion is a new participatory model for adolescent public health services. Implications: This innovation provides a replicable framework for other communities to strengthen adolescent health education through digital engagement. Highlights:• Digital game media improves youth stunting awareness• Increased cadre participation in Posyandu Remaja activities• Innovative model for community-based adolescent health education